2017
DOI: 10.3389/fchem.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Histidine Phosphotransferase Plays a Crucial Role in Photomorphogenesis and Pathogenesis in Magnaporthe oryzae

Abstract: Two-component signal transduction (TCST) pathways play crucial roles in many cellular functions such as stress responses, biofilm formation, and sporulation. The histidine phosphotransferase (HPt), which is an intermediate phosphotransfer protein in a two-component system, transfers a phosphate group to a phosphorylatable aspartate residue in the target protein(s), and up-regulates stress-activated MAP kinase cascades. Most fungal genomes carry a single copy of the gene coding for HPt, which are potential anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We also found AS events derived from MoPTEN , a gene that was shown to produce two transcripts, in our RNA-seq data. One isoform ( MoPTEN-1 ) is involved in conidiation and appressorial formation while the second ( MoPTEN-2 ) is needed for invasive hyphal growth [ 39 ], suggesting that motif changes caused by AS made them perform different functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found AS events derived from MoPTEN , a gene that was shown to produce two transcripts, in our RNA-seq data. One isoform ( MoPTEN-1 ) is involved in conidiation and appressorial formation while the second ( MoPTEN-2 ) is needed for invasive hyphal growth [ 39 ], suggesting that motif changes caused by AS made them perform different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Two M. oryzae genes subjected to AS, including MoYPD and MoSOM1 , contribute to virulence [ 37 , 38 ]. Two AS isoforms derived from MoPTEN , a gene important for growth and pathogenesis, seem to perform distinct functions [ 39 ]. A previous study investigated AS profiles in an M. oryzae (previously called M. grisea ) strain by sequencing expressed sequence tags (ESTs) [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a specialized type of MAPKs in fungi and mammalian was termed as stress-activated protein kinases (SAPKs), as it is responsible for stress response, including heat shock, hyperosmolarity, ultraviolet (UV) light irradiation, and oxidative stress ( Brown et al, 2014 ). Examples of SAPKs from fungi include Magnaporthe oryzae YPD1 regulating penetration and conidiation ( Mohanan et al, 2017 ), Mycosphaerella graminicola Hog1 involved in osmosensitivity and dimorphic transition in fungal pathogenicity ( Mehrabi et al, 2006 ), and Bipolaris oryzae SRM1 for tolerance to hyperosmolarity, hydrogen peroxide (H 2 O 2 ), and UV exposure ( Moriwaki et al, 2006 ). On the other hand, mammalian p38s and JNKs are involved in the inflammatory and stress responses ( Kyriakis et al, 2004 ; Chadee and Kyriakis, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aerial hyphal differentiation and conidial development were controlled by a light–dark cycle in P. oryzae . Of seven genes encoding light-sensitive proteins ( PoWC-1 , TWL , TIG1 , GCN5 , YPD1 , PoSIR2 , and TRX2 ) ( Lee et al, 2006 ; Ding et al, 2010 ; Fernandez et al, 2014a ; Deng et al, 2015 ; Zhang et al, 2016 , 2017 ; Mohanan et al, 2017 ), two genes ( PoSIR2 and TRX2 ) were found to be significantly up-regulated in Δ Pogpd2 under a light–dark cycle (increased to 1.5- and 1.6-fold), but not in a continuous dark condition ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%